Chimpanzees in biomedical and behavioral research : assessing the necessity - Altevogt, Bruce M. (National Academies Press, 2011)
"For many years, experiments using chimpanzees have been instrumental in advancing scientific knowledge and have led to new medicines to prevent life-threatening and debilitating diseases. However, recent advances in alternate research tools have rendered chimpanzees largely unnecessary as research subjects. The Institute of Medicine, in collaboration with the National Research Council, conducted an in-depth analysis of the scientific necessity for chimpanzees in NIH-funded biomedical and behavioral research. The committee concludes that while the chimpanzee has been a valuable animal model in the past, most current biomedical research use of chimpanzees is not necessary, though noted that it is impossible to predict whether research on emerging or new diseases may necessitate chimpanzees in the future"--Publisher description.